Preparation and Characterization of Nickel ferrite Nanoparticles via Co-precipitation Method - Sagadevan, Suresh; Chowdhury, Zaira Zaman; Rafique, Rahman Faizur (Associacao Brasileira de Metalurgia e Materiais (ABM); Associacao Brasileira de Ceramica (ABC); Associacao Brasileira de Polimeros (ABPol), 2018)
Nickel ferrite (NiFe2O4) nanoparticles were synthesized using co-precipitation method. The X-ray diffraction (XRD) pattern was used to determine the structure of NiFe2O4 nanoparticles. The presence of NiFe2O4 nanoparticles was confirmed by the FT-IR spectrum. The details of the surface morphology of NiFe2O4 nanoparticles were obtained by Scanning Electron Microscopic analysis. The particle size of the NiFe2O4 nanoparticles could be determined by means of Transmission Electron Microscopy. This work aimed at the investigation of the dielectric properties such as the dielectric loss and the dielectric constant of NiFe2O4 nanoparticles at varied frequencies and temperatures. In addition, the magnetic properties of the NiFe2O4 nanoparticles were studied.